Co-participation in physical activity: perspectives from Australian parents of pre-schoolers. (19th March 2020) - Hnatiuk, Jill A; Dwyer, Genevieve; George, Emma S; Bennie, Andrew
Abstract: Co-participation in physical activity may be important for helping families with young children meet physical activity recommendations. Yet, little is known about what families perceive to be the benefits, barriers and facilitators of co-participation. This study explored (i) parents' perceptions about physical activity and possible benefits of family-based co-participation in physical activity, (ii) their perceived facilitators and barriers to co-participation and (iii) their recommendations for improving co-participation within their community. Fifteen parents (14 mothers, 1 father) of 2- to 4-year-old children residing in Western Sydney, Australia, participated in one-on-one interviews between September 2016 and January 2017. Interviews were audio-recorded and transcribed verbatim. Four main themes and seven sub-themes emerged from the thematic analysis of the interview data. When parents were asked to reflect on their understanding of physical activity, they discussed a range of well-known activities (e.g. active play, active transport) and also reported 'anything but screen time'. The major benefits parents reported about co-participation were spending quality time together, improving children's general health and well-being and the development of physical skills. Social (e.g. social networks, negative stereotypes) and environmental (e.g. home space, neighbourhood design, shading) facilitators and barriers were identified, yet their impact on co-participation often varied depending on the presence (or lack thereof) of other factors in the physical or social environment. Key recommendations suggested by parents included improvements to home outdoor spaces, neighbourhood design and play spaces and community services.